Determinants of Sustainability of Rural Agricultural Projects in Rwanda: Case of Maize Projects in Budubi Irrigation Scheme in Nyanza District - Alice, MUHONGERWA (International Journal of Scientific Research and Management (IJSRM), 2021)
This study aimed at assessing the influence of financial input on the sustainability of maize projects in Budubi Irrigation Scheme; to investigate influence of Irrigation Scheme management on the sustainability of maize projects in Budubi Irrigation Scheme; to examine influence of benefits from maize on the sustainability of maize projects in Budubi Irrigation Scheme and to assess influence of care for environment on the sustainability of maize projects in Budubi Irrigation Scheme. The study was guided by the sustainability theory and applied a descriptive cross-sectional design, and population of 392 persons out of which a sample of 198 was applied. Document review, questionnaire, interview, and observation methods were used to collect data, while descriptive statistics and content analysis was applied for data analysis.Key words: Irrigation scheme, sustainability, agricultural projects, Maize projects.